PROFIL HUBUNGAN SOSIAL PESERTA DIDIK KELAS UNGGUL DI SMP NEGERI 12 PADANG - Priawan, Randy Okta (Bimbingan dan Konseling, 2014)
This research was caused by the excellent studentsâ class skill in building the socialrelationship in SMP N 12 Padang which have obstacle at school environment with others students orteachers. The purposes of this research were to describe how is the profile of social relationship ofexcellent class in school environment with same age students and teachers. This research wasqualitative research with descriptive study which describe the signs, fact and reality that comes as inthe field about social relationship of excellent class in SMP N 12 Padang. The informants of thisresearch were 3 students of excellent class, 3 students of regular class, 3 class advisors or teachers andcounselor. The instrumentation used in this research is interview. The techniques used in processingdata were reduction data, presenting data and making conclusion. The result of this research showedthat excellent class students have obstacle in doing social relationship at school environment withsame age students in excellent class and also with students in regular class. The location of excellentclass and regular class is far and it caused both of students have bad social relationship because theyoften to communicate each other in school environment. Besides, the excellent class students alsohave obstacle in doing social relationship with the teachers in school environment, so this conditioncaused the closeness of students and teacher insufficient.